Bureaucratic Reform in an Era of Uncertainty and Change: Relinquish the Bureaucratic Polity Model by Evolving Governance - Ramadhan, Naufal Hanif; Isbandono, Prasetyo; Prastyawan, Agus; Rahayu, Eka Puji (KnE Social Sciences, 2022)
“Public policy is intellectual activities in the political process” – Prof. Eko Prasojo The pandemic’s shockwave has reverberated around the world, shocking government agencies at all levels of concern, including health, economics, technology, tourism, and industry. These occurrences signal the start of the VUCA era, which can be defined as the world we live in today, in which change is rapid, unpredictable, and influenced by a variety of difficult-to-control factors, and truth and reality have become highly subjective. In this context, government bureaucrats are confronted with a slew of challenges. Because the legitimacy of government supremacy in politics cannot be avoided, bureaucratic reform is becoming increasingly difficult. After all, the bureaucratic system in Indonesia is still classified as a bureaucratic polity model, according to Karl D. Jackson, in which policymaking is based on political interests and proximity to stakeholders. This is demonstrated by the fact that most seats in government institutions are held by groups with political backgrounds, which will, of course, have an impact on policymaking. To respond to these dynamics, an ideal and measurable special treatment is required. The results of the Government’s evaluation in dealing with the bureaucracy served as the primary source of information in this research for considering the major points of bureaucratic reform. The main proposal developed is to improve state governance by abandoning the bureaucratic-polity model. These efforts can be carried out in the following ways: (1) bad governance will be improved through the development of governance 2.0 with the values of collaborative governance and good governance; (2) Indonesia’s multi-level governance packaged in the regional autonomy system prevents the Central Government from intervening deeply, necessitating a strategy that is evenly distributed in all sectors, namely by implementing minimum policies at the evidence-based policy level; and (3) in the VUCA era, which is characterized by uncertainty and change, this bottom-up transformation must be accompanied by a strategy to establish a communication corridor that connects all parts of the country. Keywords: bureaucratic reform, VUCA era, governance 2.0, bureaucratic polity, public policy